Nanoparticles and the environment - Banfield, Jillian F.; Navrotsky, Alexandra (Reviews in mineralogy and geochemistry, 2018)
Volume 44 of Reviews in Mineralogy and Geochemistry contains descriptions of the inorganic and biological processes by which nanoparticles form, information about the distribution of nanoparticles in the atmosphere, aqueous environments, and soils, discussion of the impact of size on nanoparticle structure, thermodynamics, and reaction kinetics, consideration of the nature of the smallest nanoparticles and molecular clusters, pathways for crystal growth and colloid formation, analysis of the size-dependence of phase stability and magnetic properties, and descriptions of methods for the study of nanoparticles. These questions are explored through both theoretical and experimental approaches. This volume was prepared in conjunction with a short course, "Nanoparticles in the Environment and Technology," convened on the campus of the University of California, Davis, CA on December 8 and 9, 2001